Risk of autism spectrum disorder in children with infantile epileptic spasms syndrome: a retrospective study in a single center in Brazil - Marília Barbosa de Matos; Paulo Breno Noronha Liberalesso; Tiago dos Santos Bara; Paula Carolina Martins Alves Gomes; Bianca Simone Zeigelboim; Jair Mendes Marques; Mara L. Cordeiro (Elsevier, 2024)
Objective: This study aimed to investigate the prevalence of autism spectrum disorder and its possible correlations with clinical characteristics in patients with infantile epileptic spasms syndrome in a single center in Brazil. Methods: This retrospective cross-sectional study examined 53 children with the diagnosis of infantile epileptic spasms syndrome prior to an autism spectrum disorder assessment. Participants were divided into two groups based on the presence or absence of autism spectrum disorder. Available variables (sex, medications, median age at onset of infantile epileptic spasms syndrome, and presence of comorbidities) were compared using Mann-Whitney U or chi-square tests. Results: Among the included patients, 12 (23 %) were diagnosed with autism spectrum disorder, corresponding to a relative risk of 0.29 (95 % confidence interval 0.174-0.492). The age at the first seizure ranged from 3 to 15 months, with a mean of 6.65 months. This age significantly differed between participants with autism spectrum disorder (10.58 months) and those without (5.43 months), p<0.001. Conclusion: Children with infantile epileptic spasms syndrome have a higher risk of being diagnosed with autism spectrum disorder. Later age of onset and period of spasm occurrence might be predisposing risk factors.